ANALYSIS OF STUDENT ERRORS IN SOLVING HIGHER ORDER THINKING SKILLS PROBLEMS IN BUILDING MATERIALS - Feri Istikhomah; Supriyono Supriyono; Rintis Rizkia Pangestika (The University of Kuningan, 2022)
ABSTRACT This study aims to 1) describe the types of errors made by students in solving HOTS type story questions on building material, 2) describe the factors that cause students to make mistakes in solving HOTS type story questions on building materials. The type of research used in this research is descriptive qualitative using qualitative methods. The research subjects were the fifth grade students of Pringgowijayan Elementary School in the academic year 2021/2022 with a total of 12 students. The data collection technique in this study used the test method, interview method and documentation. The data obtained are in the form of student answer sheets and interview transcripts. The data collection instrument that became the main instrument was the researcher himself who was supported by a HOTS test, a voice recorder, and an outline interview guide. Data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. The results showed 5 types of errors made by students in solving HOTS questions, namely 1) reading errors in the form of student answers that were not in accordance with the intent of the question and incorrectly used information on the questions; 2) misunderstanding in the form of mistaking the information in the question and not knowing what is known and asked from the question; 3) transformation errors in the form of incorrectly converting information into mathematical models, not writing down the steps for solving problems, and incorrectly determining arithmetic operations; 4) process skill error in the form of an error in the calculation process and not writing down the steps for solving the problem; 5) notation error in the form of an error in writing the conclusion of the answer.Keywords: error, causative factor, HOTS